2006
DOI: 10.1128/jb.00259-06
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Substrate Specificity of Aminopyrrolnitrin Oxygenase (PrnD) by Mutational Analysis

Abstract: Molecular modeling and mutational analysis (site-directed mutagenesis and saturation mutagenesis) were used to probe the molecular determinants of the substrate specificity of aminopyrrolnitrin oxygenase (PrnD) from Pseudomonas fluorescens Pf-5. There are 17 putative substrate-contacting residues, and mutations at two of the positions, positions 312 and 277, could modulate the enzyme substrate specificity separately or in combination. Interestingly, several of the mutants obtained exhibited higher catalytic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…All three mutations identified in our study did not result in significant alteration in the side chain size or the hydrophobicity, and yet they significantly affected the binding of lauroyl-CoA. It is not atypical in protein engineering that small changes in active site residues play a significant role in altering protein substrate specificity (36,37). In the case of PhlD, more drastic changes of tunnel residues than what was found in this study might not even be desired because they could affect the correct folding of the tunnel and consequently damage the overall activity of PhlD.…”
Section: Discussionmentioning
confidence: 68%
“…All three mutations identified in our study did not result in significant alteration in the side chain size or the hydrophobicity, and yet they significantly affected the binding of lauroyl-CoA. It is not atypical in protein engineering that small changes in active site residues play a significant role in altering protein substrate specificity (36,37). In the case of PhlD, more drastic changes of tunnel residues than what was found in this study might not even be desired because they could affect the correct folding of the tunnel and consequently damage the overall activity of PhlD.…”
Section: Discussionmentioning
confidence: 68%
“…12 value is in the same range as the activity of the other known N-oxygenase PrnD. 17 The comparatively low in vitro value is partly due to the lower temperature but for the most part a consequence of the special reaction conditions. 13…”
Section: Structure and Activity Determinationmentioning
confidence: 91%
“…PCRbased detection revealed that none of the 18 endophytic isolates harbored specific genes involved in the biosynthesis of the antibiotics 2,4-diacetylphloroglucinol, phenazines, and pyoluteorin; the lack of production of these three antibiotics was confirmed by RP-HPLC analysis of culture extracts of the 18 endophytic isolates (data not shown). PCR-based detection of prnD, one of the four genes involved in pyrrolnitrin biosynthesis (48), and TLC analyses revealed that the endophyte Pseudomonas sp. strain ESR94 and eight of the endophytic Burkholderia isolates produced the antibiotic pyrrolnitrin (Table 3; Fig.…”
Section: Resultsmentioning
confidence: 99%